DIGITAL TRANSFORMATION OF THE HEALTHCARE SYSTEM AS A MEANS OF PROVIDING QUALITY MEDICAL CARE TO THE POPULATION OF RURAL AREAS OF UKRAINE - Bugaiev, Vladyslav (SWorldJournal, 2025)
The article considers the digital transformation of the healthcare system in rural areas of Ukraine as a means of improving the accessibility, effectiveness and equity of healthcare. The current state of digitalization is analyzed, the main challenges are